School Leadership Style And Organizational Culture On Teacher Performance Of Junior High Schools In Bandar Lampung - Arista, Mega (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to determine the effect of the principal's leadership style, organizational culture on the performance of teachers at Muhammadiyah 3 Junior High School in Bandar Lampung. This research uses a quantitative approach. Data collection techniques in this study using a questionnaire. The analysis used in this study is using regression analysis to test the influence between the independent variable on the dependent variable. The results of this study assessed by teachers as respondents have very good results, namely the average or mean 80, median with a score of 80, mode 80. Judging from the calculation of the regression equation with the results of a significant value of 0.000 <0.005. t count value 4.375> t table 2.03693. So it means that there is a significant influence between the principal's leadership style on teacher performance. The constant B1 is positive, then the principal's leadership style has a positive effect on teacher performance by 0.395 or 39.5%.